Laparoscopic ventricular-cholecystic shunt - Romeo C. Ignacio, Jr; Sophia M.V Schermerhorn; Alexander J. Marrotte; James M. Prieto (Elsevier, 2019)
Since the first reported case in 1959, ventricular cholecystic (VC) shunts have been used as an alternative treatment for hydrocephalus, most often used in the event of ventriculoperitoneal shunt failure. To date, all surgical placements of VC shunts have been performed using an open operative technique. This case report describes the laparoscopic placement of a VC shunt in a 20-month-old male child. A three-year follow-up appointment after surgery demonstrated no reported complications. We describe the first documented laparoscopic technique for this procedure and discuss a decision algorithm for VC shunts as well as some of the benefits of this minimally invasive approach. Keywords: Ventricular cholecystic shunt, Ventricular gallbladder shunt, Ventriculobiliary shunt